Rigid tetrazine fluorophore conjugates with fluorogenic properties in the inverse electron demand Diels-Alder reaction - Wieczorek, Achim; Buckup, Tiago; Wombacher, Richard (Organic & biomolecular chemistry, 2014)
1,2,4,5-Tetrazine fluorophore derivatives with structurally rigid molecular designs were synthesized using Sonogashira and Stille cross-coupling as well as copper-catalyzed azide-alkyne cycloaddition. The synthesized bichromophoric systems exhibit low fluorescence quantum yields due to quenching by the tetrazine. The extent of fluorescence quenching observed for those systems was shown to depend on the distance between the fluorophore and the tetrazine. The decreased fluorescence is “turned on” by conversion of the tetrazine in the inverse electron demand Diels-Alder cycloaddition. Time resolved spectroscopy indicated resonance energy transfer between BODIPY and the tetrazine as the underlying quenching mechanism. The synthesized conjugates were successfully applied in protein labeling experiments.